Sesquiterpenoids from Stem Bark of Chisocheton lasiocarpus and Their Cytotoxic Activity against MCF-7 Breast Cancer Cell - Unang Supratman; Samuel San Parulian; Nurlelasari Nurlelasari; Al Arofatus Naini; Tri Mayanti; Erina Hilmayanti; Desi Harneti; Darwati Darwati; Rani Maharani; Kindi Farabi; Risyandi Anwar; Sofa Fajriah; Muhamad Nurul Azmi; Yoshihito Shiono (Universitas Jenderal Soedirman, 2022)
Sesquiterpenoids are derivatives of terpenoid compound that have a diverse skeleton and broad spectrum of biological activities, particularly anticancer activity. This research reported the isolation and elucidation structure of sesquiterpenoid from Chisocheton lasiocarpus stem bark, as well as their cytotoxic activity. Four sesquiterpenoid compounds, namely eudesm-4(15)-ene-1β,6β-diol (1), allo-aromadendrane-10α,14-diol (2), allo-aromadendrane-10β,14-diol (3) and guaianediol (4), were isolated for the first time from Chisocheton lasiocarpus stem bark. The chemical structure of all compounds was identified by spectroscopic analysis, including IR, MS, 1H-NMR, 13C-NMR and DEPT, and compared with previous reported spectral data. The cytotoxic activity of the isolated compounds against MCF-7 breast cancer line were examined by using the resazurin method. The results showed compound 1 shown the highest cytotoxic activity with IC50 108.08 ± 0.58 µM.